The unstoppable Wasp!. Unstoppable!. #2 - Whitley, Jeremy (Spotlight, 2020)
Nadia Pym, a.k.a. the Wasp, recruits Taina Miranda, a girl with a special talent for robotics for her lab and joins forces with Moon Girl to battle a giant rat.